Characteristics of Residential Tracker Accuracy in Quantified Direct Beam Irradiance and Global Horizontal Irradiance - Sabry, M S.; Raichle, B W. (Journal of Technology Innovations in Renewable Energy, 2014)
An accurate solar tracker matches array angles with solar angles throughout the day. Many studies have used the power produced by a tracked PV array as a proxy to characterize a tracker’s accuracy. However, it is difficult to decouple the effects of tracker performance from other effects on power output. It was not found in the literature reviewed that there are studies that determine the accuracy of solar trackers by directly measuring the tracker angles. This study was an experiment to determine the accuracy of two small commercially available non-algorithm based solar trackers: the Zomeworks UTR-020 passive one axis solar tracker, and the Wattsun AZ-225 active electro-optical two axis solar tracker. Accuracy of the trackers was determined by measuring the tracking angles under varying conditions including direct beam irradiation (DBI) and global horizontal irradiance (GHI), and comparing to calculated sun angles. The results showed that the average azimuth angle accuracy of the Zomeworks UTR-020 is 75%, the average azimuth angle accuracy of the Wattsun AZ-225 is 88%, and the average elevation angle accuracy of the Wattsun is 89%. In addition, the results showed a weak correlation between the azimuth accuracy of the Zomeworks and DBF, a strong correlation between the azimuth accuracy of the Wattsun and DBF, and a moderate correlation between the elevation accuracy of the Wattsun and DBF. Moreover, the azimuth accuracy of the Wattsun was always higher than that of the Zomeworks under all DBF and GHI conditions.